2020
DOI: 10.3390/plants9091067
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Roles of Glutathione in Mediating Plant Defense during Biotic Stress

Abstract: Glutathione and reactive oxygen species (ROS) play important roles, within different cell compartments, in activating plant defense and the development of resistance. In mitochondria, the accumulation of ROS and the change of glutathione towards its oxidized state leads to mitochondrial dysfunction, activates cell death, and triggers resistance. The accumulation of glutathione in chloroplasts and peroxisomes at the early stages of plant pathogen interactions is related to increased tolerance and resistance. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
59
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 119 publications
(420 reference statements)
8
59
0
2
Order By: Relevance
“…4 , 5 , Tables 3 , 4 , Supplementary Tables S2 , S3 ). Similar results were recorded in other plants under conditions of high light stress, infection, dark-induced senescence or total nutrient deficiency 6 , 29 , 49 , 50 . Chloroplast degradation may be due to the significant decrease in N in the mature leaves of each scion/rootstock combination following the extensive remobilization of N present in the cell to younger leaves or storage areas during nutrient deficiency 51 , 52 (Figs.…”
Section: Resultssupporting
confidence: 88%
“…4 , 5 , Tables 3 , 4 , Supplementary Tables S2 , S3 ). Similar results were recorded in other plants under conditions of high light stress, infection, dark-induced senescence or total nutrient deficiency 6 , 29 , 49 , 50 . Chloroplast degradation may be due to the significant decrease in N in the mature leaves of each scion/rootstock combination following the extensive remobilization of N present in the cell to younger leaves or storage areas during nutrient deficiency 51 , 52 (Figs.…”
Section: Resultssupporting
confidence: 88%
“…2 and 3). Similar results were recorded in other plants under conditions of high light stress, infection, dark-induced senescence or total nutrient de ciency 6,20,45,46 . Chloroplast degradation may be due to the signi cant decrease in N in the mature leaves of each scion/rootstock combination following the extensive remobilization of N present in the cell to younger leaves or storage areas during nutrient de ciency 47,48 ( Tables 2 and 3; Fig.…”
Section: Effect Of Rootstock Ploidy Level On Anatomical Properties Ofsupporting
confidence: 86%
“…Plastoglobuli are bound to thylakoids via their membranes. Studies have shown that plastoglobuli are involved in the formation and degradation of thylakoids during plant growth, development and senescence but also when plants are exposed to drought, high-light, N starvation or fungal infection 46,[51][52][53] . The reduced damage of the thylakoid membrane in C/CM4x would explain the maintenance of the plastoglobuli numbers and the small increase in their size due to the accumulation of catabolites formed by thylakoid degradation in their hydrophobic core compared to other scion/rootstock combinations 54,55 ( Tables 2 and 3; Fig.…”
Section: Effect Of Rootstock Ploidy Level On Anatomical Properties Ofmentioning
confidence: 99%
“…It plays a role as a non-enzymatic antioxidant in the ascorbate-glutathione cycle, and participates in many detoxification reactions in plants [60][61][62]. Furthermore, GSH is also known as a central regulator of plant signaling during plant-pathogen interactions [63,64].…”
Section: Glutathione (Gsh) In Plant Disease Resistancementioning
confidence: 99%